Parameter Tuning of a Distributed Model Predictive Controller for Water Delivery Canal Application - Igreja, José (2012)
This work addresses the problem of tuning the parameters of a distributed model predictive control algorithm (DMPC) applied to the control of water level in a water delivery canal. The D-SIORHC algorithm considered is based on distributed MPC control agents that incorporate stability constraints. Coordination of the different controllers is achieved by a negotiation among neighbor agents. The value of the controller parameters that yield the best performance is obtained by comparing the experimental results obtained from different field tests.